Culling Layer Hen Gastrointestinal Helminth Identification at Wonokromo Market Surabaya - Fakhryyah Maharani Deviyanti; Hastutiek, Poedji; Arimbi; Mufasirin; Permata Sari, Dian Ayu; Sunarso, Agus (Journal of Parasite Science, 2023)
This study aimed to find out and identification gastrointestinal species parasites in cullinglayer hen which sold at in the Wonokromo traditional market Surabaya City. The samples were100 culling layer hen purchased from five merchant. Research design with purposive sampling.The samples was examined by having surgery through the digestive tract and fecal examination.Meanwhile, fecal examination used native methods, sediment and floating. Types of wormsidentified were Ascaridia galli, Heterakis gallinarum, Raillietina tetragona and Mediorhynchusgallinarum through examination the digestive tract surgery. There were Ascaridia galli, Heterakisgallinarum, and Raillietina sp. found in examination of worm egg in fecal. The prevalence ofparasite gastrointestinal in the culling layer hen in sold at in the Wonokromo traditional marketSurabaya City was 85%. The difference in percentage rates were likely due to seasonal factors,maintenance management, feeding and ranching systems.